Fpga based reprogrammable motherboard & daughter board circuits design and applications - İlaslan, Muhammet Furkan (Institute of Science and Technology, 2020)
The number of students who want to improve theirselves or amateur users who inerested in hobby purposes has increased as well as professional users. In this thesis, it is tried to produce a new ready-made hardware kit with strong hardware components due to the insufficiency of the ready-made hardware kits in high-speed applications and the low professional framework. In addition, an ergonomic design was targeted with the aim of training kit and auxiliary additional circuit prototype was designed to perform certain tasks. For this purpose, the circuit design has been explained step by step for the users who want to improve themselves professionally, the important details and the information to be used in the data sheets used have been mentioned, the information has been presented about the operation of the circuit by making an application. Altium: PCB Design Software & Tools program was used in the drawings of the circuit. Also, the ISE Design Suite: WebPACK Edition program was used for the use of FPGAs of the Xilinx company. JTAG interface has been used to install the programs. Two prototypes were produced as a mother board and auxiliary board that is also called the daughterboard. Since the motherboard, which has a four-layer structure, is the main body that performs the basic operations, unnecessary circuit elements are avoided on the board. The motherboard consists of three power units, three regulators, an FPGA, a PROM, an oscillator, five LEDs, two buttons, 2x5 collectors for a JTAG cable, two pieces 2x8 collectors for connection with the designed daughterboard, resistors, and capacitors that have been added to the circuit sufficiently by making calculations. It is especially important that the FPGA and PROM components are manufactured by the same company and therefore they have selected in terms of performance of the designed circuit and the compatibility of the elements. The auxiliary circuit board is designed to convert from the digital signal to the analog signal and from the analog signal to the digital signal. Therefore, the main circuit elements used on this card are ADC and DAC. The fact that ADC and DAC elements have the same physical properties enabled symmetrical design. In addition, both converters, 8 channels, 12-bit, compatibility problems were avoided.
Fpga tabanlı tekrar programlanabilir ana & yardımcı devre kart tasarımı ve uygulamaları
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: microprocessors; microcontrollers; hardware description languages; components of motherboard